Dynamic evolution of Achromobacter xylosoxydans in a patient with leukemia receiving antibiotic treatment - Traglia, German Matias (2024)
Multidrug-resistant Achromobacter xylosoxidans (Ax) is responsible for numerous infections affecting immunocompromised and cystic fibrosis patients. Genetic changes often drive the evolution of antimicrobial resistance. A patient with leukemia infected with a strain, Ax114, susceptible to meropenem, ceftazidime/avibactam, and cefiderocol, was initially treated with meropenem. After this course, a strain resistant to meropenem, Ax115, was isolated. A second course with ceftazidime/avibactam was followed by the isolation of a strain, Ax130, characterized by resistance to ceftazidime/avibactam and reduced susceptibility to cefiderocol. Multilocus sequence typing and phylogenetic analysis using core genes and variant calling analyses revealed that all three isolates were genetically related, suggesting a common origin, and belonged to sequence type 184 (ST184). The mutations potentially most relevant to drug resistance were those identified in the genes penA (one transversion and one transition, Ax130) and eal (one transversion, Ax115 and Ax130). The former gene encodes the peptidoglycan D,D transpeptidase, and the latter codes for a hydrolase that catalyzes c-di-GMP degradation and is associated with virulence and biofilm formation. Strains Ax115 and Ax130 acquired a class 1 integron that harbors the aadB-blaoxa-2 gene cassette in the variable region. Transcriptomic analysis also showed that blaAXC-1 (intrinsic β-lactamase) expression is higher in Ax115 and Ax130 than in Ax114. The results strongly suggest that the antibiotic treatments primarily selected Ax115 and Ax130.